2002
DOI: 10.1021/ma011366e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Copolymerization of Ethylene and Polar and Nonpolar α-Olefins in Emulsion

Abstract: Novel P,O-chelated Ni(II) catalysts for ethylene and R-olefins polymerization have been used for the copolymerization of ethylene with various long-chain R-olefins in emulsion. Nonfunctionalized R-olefins have been copolymerized with ethylene using miniemulsion to disperse the catalyst at the nanometric level. The influence of the comonomer on catalyst performances as well as latex properties has been analyzed. High comonomer incorporation and stable latex of 30% solid content can be achieved by this method. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 45 publications
1
56
0
1
Order By: Relevance
“…Especially in the case of group 4, these new catalysts and cocatalyst/activators have achieved great success in the production of advanced polyolefin materials [4]. The new systems are able to control product molecular weight, polydispersity, comonomer enchainment level and pattern, the tacticity of poly(a-olefins) [17,56,57], copolymerization of olefins with polar comonomers (group 10) [54,55,[58][59][60][61][62], and the catalytic synthesis of block copolymers by processes such as chain shuttling polymerization [63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the case of group 4, these new catalysts and cocatalyst/activators have achieved great success in the production of advanced polyolefin materials [4]. The new systems are able to control product molecular weight, polydispersity, comonomer enchainment level and pattern, the tacticity of poly(a-olefins) [17,56,57], copolymerization of olefins with polar comonomers (group 10) [54,55,[58][59][60][61][62], and the catalytic synthesis of block copolymers by processes such as chain shuttling polymerization [63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other types of polymerizations can also be carried out in miniemulsion: the anionic polymerization in nonaqueous miniemulsions leads to polyamide nanoparticles, 21 and in aqueous phase, polybutylcyanoacrylate (PBCA) nanoparticles can be synthesized. 22 The cationic polymerization allows the formation of poly-p-methoxystyreneparticles, 23,24 the catalytic polymerization enables the synthesis of polyolefine 25,26 or polyketone particles, 27 the ring-opening metathesis polymerization leads to polynorbonene nanoparticles, 28,29 and the step-growth acylic diene metathesis (ADMET) polymerization to oligo(phenylene vinylenes) particles. 30 The polyaddition in miniemulsion allows the formation of polyepoxides 31 or polyurethanes (PUs) particles.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…For the case of low-crystalline (and in the example studied also low molecular-weight) ethylene-1-olefin copolymers, which have a much higher miscibility with the organic phase present in the miniemulsion droplets (in this case 1-olefin copolymer and some aromatic solvent), Claverie et al have shown that the number of polymer particles obtained is equal to the number of miniemulsion droplets initially present. [14] Water-soluble Catalysts An alternative for the above miniemulsion procedure is the utilization of water-soluble catalyst precursors. In this case, the initial reaction mixture is a single homogeneous aqueous phase, containing surfactant and catalyst.…”
Section: Polymerization With Catalyst Miniemulsionsmentioning
confidence: 99%
“…[13] Crystallinity can be reduced by copolymerization, albeit at a further expense of molecular weight and also reduced catalyst activities by comparison to ethylene homopolymerization. [14,15] Polymerization with well-defined complexes as a catalyst precursor as well as with in situ prepared catalysts has been studied. The latter in situ catalysts can be prepared entirely from commercially available components, [15] in addition the catalyst is also quite robust in terms of handling and stability under polymerization conditions.…”
mentioning
confidence: 99%